Peningkatan Kemampuan Memasang Kaus Kaki Melalui Teknik Task Analysis Pada Anak Dengan Down Sydrome - Asnitha M. Banjarnahor; Rahmahtrisilvia Rahmahtrisilvia; Marlina Marlina; Antoni Tsaputra (Lembaga Riset dan Inovasi Almatani, 2026)
This study aimed to improve the sock-wearing skills of children with Down syndrome through the implementation of the task analysis technique. The research employed a Classroom Action Research (CAR) design conducted in Grade I at SLB Negeri Simalungun. The research subjects consisted of two students with Down syndrome, identified as EVT and NPS. Based on the initial assessment, the students’ ability to wear socks was categorized as low, with achievement percentages of 37% for EVT and 43% for NPS. The study was carried out in two cycles, each consisting of three meetings. In Cycle I, the application of the task analysis technique resulted in an improvement in sock-wearing skills, with EVT’s performance increasing from 47% to 63%, while NPS showed improvement from 53% to 73%. Furthermore, in Cycle II, EVT demonstrated more optimal improvement, reaching a range of 73%–85%, whereas NPS showed a stable increase within the range of 80%–88%. Data were collected through observation using a self-care skills assessment sheet, and data analysis was conducted using descriptive quantitative analysis by comparing results across cycles. The findings indicate that the task analysis technique is effective in improving self-care skills, particularly sock-wearing abilities, in children with Down syndrome. This study confirms that learning activities structured in a gradual and systematic manner can support children with Down syndrome in understanding and performing self-care activities more independently in accordance with their developmental characteristics.